Functional Characterization of a Novel IRF6 Frameshift Mutation From a Van Der Woude Syndrome Family - Zhang, Mengqi; Zhang, Jieni; Zhao, Huaxiang; Ievlev, Vitaly; Zhong, Wenjie; Huang, Wenbin; Cornell, Robert A.; Lin, Jiuxiang; Chen, Feng (Frontiers in Genetics, 2020)
Background: Loss-of-function mutations in interferon regulatory factor-6 (IRF6) are responsible for about 70% of cases of Van Der Woude Syndrome (VWS), an autosomal dominant developmental disorder characterized by pits and/or sinuses of the lower lip and cleft lip, cleft palate, or both. Method: We collected a Chinese Han VWS pedigree, performed sequencing and screening for the causal gene mutant. Initially, species conservation analysis and homology protein modeling were used to predict the potential pathogenicity of mutations. To test whether a VWS family-derived mutant variant of IRF6 retained function, we carried out rescue assays in irf6 maternal-null mutant zebrafish embryos. To assess protein stability, we overexpressed reference and family-variants of IRF6 in vitro. Results: We focused on a VWS family that includes a son with bilateral lip pits, uvula fissa and his father with bilateral cleft lip and palate. After sequencing and screening, a frameshift mutation of IRF6 was identified as the potential causal variant (NM.006147.3, c.1088-1091delTCTA; p.Ile363ArgfsTer33). The residues in this position are strongly conserved among species and homology modeling suggests the variant alters the protein structure. In irf6 maternal-null mutant zebrafish embryos the periderm differentiates abnormally and the embryos rupture and die during gastrulation. Injection of mRNA encoding the IRF6 reference variant of human IRF6, but not of the frame-shift variant, rescued such embryos through gastrulation. Upon overexpression in HEK293FT cells, the IRF6 frame-shift mutant was relatively unstable and was preferentially targeted to the proteasome in comparison to the reference variant. Conclusion: In this VWS pedigree, a novel frameshift of IRF6 was identified as the likely causative gene variant. It is a lost function mutation which could not rescue abnormal periderm phenotype in irf6 maternal-null zebrafish and which causes the protein be unstable through proteasome-dependent degradation.